High temperatures and CO2 dissolution can cause nitrogen losses from urine stabilized with base - Randall, Dyllon G.; Brison, Antoine; Udert, Kai M. (Frontiers in Environmental Science, 2022)
Human urine is rich in valuable nitrogen which can easily be lost due to biological urea hydrolysis and subsequent ammonia volatilization. While this enzymatic reaction can be prevented by alkalizing the urine, recent studies suggest that chemical urea hydrolysis can result in substantial nitrogen losses when drying alkalinized urine at high temperatures. Furthermore, it was previously suggested that CO2 dissolution from the air used to evaporate water from alkalinized urine could result in a pH decrease to values which allows for biological urea hydrolysis and subsequent ammonia losses. This study aimed to determine the kinetics of chemical urea hydrolysis in alkalinized human urine and confirm the effect of CO2 dissolution with controlled laboratory experiments. We measured the change in urea concentration at different temperatures and pH values for real human urine and determined the corresponding rate constants for chemical urea hydrolysis. We showed that the rate constant increases as a function of temperature and that pH has a negligible effect on the rate of chemical urea hydrolysis in the high pH range of alkalized urine (>11). The rate constants for chemical urea hydrolysis in a saturated calcium hydroxide solution were found to be 0.00147 d−1, 0.00595 d−1, 0.0204 d−1 and 0.0848 d−1 for temperatures of 25°C, 40°C, 55°C and 70°C, respectively. The effect of CO2 dissolution on urea hydrolysis was determined by aerating human urine alkalinized with calcium hydroxide (Ca(OH)2). In order to represent biological urea hydrolysis, urease was added to the solution. The computer simulations of the experimental results showed that CO2 dissolution and the subsequent dissociation of carbonic acid to carbonate ions, bicarbonate ions and protons is the main cause of the pH decrease, but CaCO3 precipitation, and NH3 volatilization foster the pH decrease. However, biological urea hydrolysis prevents the pH from decreasing below 9. Residual undissolved Ca(OH)2 was shown to substantially delay the pH decrease. Overall, this work provides valuable insights into the mechanisms of urea hydrolysis in alkalinized urine during dehydration, which can be used to design more efficient decentralized sanitation systems and minimize nitrogen losses.